Comparison of High Fructose Corn Syrup Versus Sucrose Consumption on Non-Alcoholic Fatty Liver Disease in Juvenile Iberian Pigs. (29th May 2020) - Johnson, Catherine; Harbottle, Brooke; Hernandez, Gabriella; Smith, Victoria; Coffin, Morgan; Noland, Trista; Dillard, Kayla; Glanz, Hunter; Fanter, Rob; Burrin, Doug; Frano, Michael La; Manjarin, Rodrigo; et al.
Abstract: Objectives: Non-alcoholic fatty liver disease (NAFLD) is a chronic metabolic disorder and the most common liver disease in pediatric populations. Epidemiological studies have observed a parallel increase in fructose consumption and incidence of NAFLD among children. The objective of this study was to compare the relative effect of inclusion of isocaloric amounts of high fructose corn syrup (66.5% fructose, 33.5% glucose) versus sucrose (50% fructose, 50% glucose) in the diet for 16 weeks on endpoints of NAFLD and insulin resistance. Methods: 30-d-old Iberian pigs were housed in pairs and randomly assigned to receive solid diets (g/kg body weight × d) of 1) control (CON; n = 6): 0 g HFCS, 0 g SUC, and 174.03 kcal metabolizable energy (ME), 2) high-fructose corn syrup (HFCS; n = 8): 31.20 g high-fructose corn syrup, 0 g sucrose and 261 kcal ME, and 3) Sucrose (SUC; n = 6): 0 g high-fructose corn syrup, 24.04 g sucrose and 261 kcal ME for 16 consecutive weeks. Results: Compared to CON, both HFCS and SUC diets increased body weight gain ( P ≤ 0.001), relative liver weight ( P ≤ 0.01) and leptin levels ( P ≤ 0.01), and decreased percentage of lean mass composition in the animals ( P ≤ 0.001). In addition, HFCS increased fasting insulin levels compared to CON ( P ≤ 0.05), and decreased percentage lean mass compared to SUC ( P ≤ 0.05). 75% of HFCS and 66.6% of SUC pigs showed histopathological lesions consistent with microvesicular steatosis with periportal or diffuse distribution. Serum markers of liver injury did not differ between diets, and none of the animals developed inflammation, hepatocellular ballooning, Mallory hyaline or necrosis in the liver. Metabolomics analysis revealed liver sorbitol and monosaccharide concentrations were higher in both the HFCS and SUC groups versus CON ( P ≤ 0.05), while adenosine monophosphate (AMP) were higher and adenosine diphosphate levels lower in the HFCS and SUC in comparison to CON ( P ≤ 0.05). Numerous phosphatidylcholines and sphingomyelins were differentially changed in the HFCS group versus CON ( P ≤ 0.05). Conclusions: Feeding diets high in either sucrose or high fructose corn syrup promoted obesity and steatosis in the animals. Further research is needed to investigate the mechanisms leading to increased insulin resistance in the HFCS group. Funding Sources: ARI #58, 873, AcornSeekers, STRIDE.